Micro- and Nano-vesicles from First Trimester Human Placentae Carry Flt-1 and Levels Are Increased in Severe Preeclampsia - Tong, Mancy; Chen, Qi; James, Joanna L.; Stone, Peter R.; Chamley, Lawrence W. (Frontiers in Endocrinology, 2017)
Background/Objectives: Preeclampsia is a life-threatening hypertensive disease affecting 3-5% of pregnancies. While the pathogenesis of preeclampsia remains unclear, it is known that placenta-derived factors trigger the disease by activating maternal endothelial cells prior to the onset of clinical symptoms. Extracellular vesicles (EVs) of different sizes extruded by the placenta may be one factor. The truncated/secreted form of Flt-1 (sFlt-1) has also been implicated in the pathogenesis of preeclampsia. We investigated whether placental EV production is altered in preeclampsia such that they induce endothelial cell activation, and whether (s)Flt-1 is involved. Methods: Macro-, micro- and nano- vesicles were collected from normal and preeclamptic placental explants, and separated by differential centrifugation. The number and size of micro- and nano- vesicles was measured by nanoparticle tracking analysis and their ability to activate endothelial cells quantified by endothelial cell ICAM-1 expression and monocyte adhesion. The levels of Flt-1 were measured by western blots and ELISA. Results: Preeclamptic placentae extruded significantly more micro- and nano- vesicles than control placentae and the extruded micro-vesicles were larger than those from control placentae. Micro- and nano- vesicles from both first trimester and term human placentae carried Flt-1 and levels were significantly increased in EVs from severe, but not mild, preeclamptic compared to normotensive placentae. All fractions of EVs from preeclamptic placentae activated endothelial cells, and for micro- and nano- vesicles, activation was reduced in the presence of exogenous VEGF, a Flt-1 neutralising antibody, or by pre-treatment with VEGF. While EV-bound VEGF constituted over 20% of the total detected VEGF secreted by preeclamptic and normotensive placentae, EV-bound Flt-1 did not significantly contribute to the total level of sFlt-1/Flt-1 released by human third trimester placentae. Discussion: Micro- and nano- vesicles extruded by human placentae carry Flt-1 across gestation and in severe preeclampsia, the levels of vesicle-bound Flt-1 are up-regulated. All fractions of preeclamptic placental EVs activated endothelial cells and for micro- and nano- vesicles, this was in part due to the ability of EV-bound Flt-1 to sequester VEGF. That placental EVs can activate endothelial cells supports the contention that EVs are one placental toxin contributing to the pathogenesis of preeclampsia.